The effect of filler adding palm kernel shell ash on durability and marshall values properties of asphalt concrete mix - Amelia Oktavia; Irza Sukmana; Yanuar Zulardiansyah Arif; Gigih Forda Nama (Journal of Engineering and Scientific Research, 2022)
Lampung  Province is one of the palm oil producers, especially in  Way Kanan Regency. Way Kanan Regency has two palm oil-producing mills, namely  PT.  Sawit  Indo Mas which is located  in Kampung Tanjung  Raja Sakti Blambangan  Umpu  and PT PLP which is located  in Kampung Bumi  Agung, Bahuga District. The two factories duce thousands of tons of Crude Palm Oil (CPO)   vegetable oil daily produced from palm fruit plants (Elaeis Guineensis Jacq, Arecaceae). From oil management, it is undeniable that it can create a lot of solid waste from the palm shell. Meanwhile, the government has not made much effort to use the waste from the waste. When managing palm fruit, palm shells cannot be processed into oil because they have a hard texture, so the shells are discarded and become waste. Then we use the shell for research material as a filler. Palm shell ash has a silicon dioxide  (SiO2) content which is also contained in Portland cement, so this content can allow the acquisition of a good asphalt mixture on the AC-BC layer. This study aims to see the effect of the effectiveness of adding shell ash fillers from palm shell waste in marshall test tests and value the resulting durability. The addition of fillers with percentages of  20%, 30%, 40%, 50%and 60%. From the results obtained from the test results in the laboratory that the addition of shell ash fillers of 40% gets better performance compared to shell ash with percentages of  20%, 30%, and 60%, with a higher state value of 1225 kg shown. In marshall testing, using palm shell ash fillers can increase the value of  KAO. So that from the marshall test, the durability value of the sample immersion at the IRS value of 0%  was 98.4% greater than the 40%, which was  91.13%. Overall, using palm shell ash fillers meets the minimum requirements of Bina Marga as an asphalt mixture. The degree of weather change in immersion durability affects the strength level of the marshall test.